2010
DOI: 10.1111/j.1600-0781.2010.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to extracorporeal photopheresis in advanced mycosis fungoides and Sézary syndrome

Abstract: Summary Background Extracorporeal photopheresis (ECP) has been utilized for more than 20 years to treat cutaneous T-cell lymphoma (CTCL), but a clinical response can take up to 9 months to manifest. This study was undertaken to determine whether clinical features, laboratory values, cytokine levels, or gene expression levels of tumor markers are useful to predict the subsequent response to ECP in CTCL patients with blood involvement. Methods Twenty-one patients with CTCL treated with ECP as monotherapy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
(87 reference statements)
0
19
0
1
Order By: Relevance
“…Comparison of cytokines, gene transcripts, and other laboratory measures of disease did not correlate with the subsequent clinical response. 66 In a more recent analysis of microRNA (miR) levels on a subset of this cohort (n 5 13), McGirt and colleagues 67 discovered that an early increase of PBMC miR-191, miR-223, and miR-342 at 3 months into ECP monotherapy predicted a clinical response to ECP at 6 and 12 months. In a large cohort of patients (n 5 98) with SS treated with ECP and immunostimulatory agents, Raphael and colleagues 63 found the following baseline differences in the CR group as compared with the nonresponse group: lower CD4/CD8 ratio (13.2 vs 44.2), lower median percentage of CD41/ CD26À cells (27.4% vs 57.2%), lower median percentage of CD41/CD7À cells (20.0% vs 41.3%), and higher median monocyte percentage (9.5% vs 7.3%).…”
Section: Predictors Of Responsementioning
confidence: 98%
“…Comparison of cytokines, gene transcripts, and other laboratory measures of disease did not correlate with the subsequent clinical response. 66 In a more recent analysis of microRNA (miR) levels on a subset of this cohort (n 5 13), McGirt and colleagues 67 discovered that an early increase of PBMC miR-191, miR-223, and miR-342 at 3 months into ECP monotherapy predicted a clinical response to ECP at 6 and 12 months. In a large cohort of patients (n 5 98) with SS treated with ECP and immunostimulatory agents, Raphael and colleagues 63 found the following baseline differences in the CR group as compared with the nonresponse group: lower CD4/CD8 ratio (13.2 vs 44.2), lower median percentage of CD41/ CD26À cells (27.4% vs 57.2%), lower median percentage of CD41/CD7À cells (20.0% vs 41.3%), and higher median monocyte percentage (9.5% vs 7.3%).…”
Section: Predictors Of Responsementioning
confidence: 98%
“…Based on these criteria, we identified 28 studies, in the majority of cases retrospective and based on single institution series. A total of 407 patients reported as erythrodermic were included (Table ) …”
Section: Extracorporeal Photopheresis For the Treatment Of Erythrodermentioning
confidence: 99%
“…In the recent study by Raphael et al ., a lower CD4/CD8 ratio, a higher percentage of monocytes, and lower numbers of circulating abnormal T cells at baseline were the strongest predictive factors for CR. McGirt et al . found that increased eosinophils and decreased percentage of Sézary cells were associated with a favorable clinical response to ECP, even if they failed to identify predictors of ECP response within the first three months of treatment.…”
Section: Extracorporeal Photopheresis For the Treatment Of Erythrodermentioning
confidence: 99%
“…Los predictores de buena respuesta para FEC como monoterapia incluyen: enfermedad T4 (eritrodermia), recuento de leucocitos < 20.000/ microL, recuento de células de Sézary entre 10 y 20%, menos de dos años desde el inicio del diagnóstico, sin grandes adenopatías, sin enfermedad visceral, no haber utilizado quimioterapia previa, sin elevación de células NK o de CD8 [29][30][31] .…”
Section: Fotoféresis Extracorpórea (Fec)unclassified